DAMPAK EKSPOR PISANG INDONESIA KE JEPANG DALAM RANGKA INDONESIA-JAPAN ECONOMIC PARTNERSHIP AGREEMENT (IJEPA) - Suci Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This is research aims to explain the impact of banana exports Indonesia to Japan with the Indonesia-Japan economic partnership agreement (IJEPA). Japan was chosen because it has a greatest trading partners of Indonesia, because Japan has a capacity and excess in improving the economic matters. Japan has a important role for Indonesia to realize the national interest of Indonesia, especially economic sector. Indonesia-Japan has gone some a bilateral, and this time already has economic cooperation between Indonesia and Japan the name is IJEPA. The sign of MoU has been done between two countries since august 2007 . Indonesia is agraris country, Indonesia has many chance to improving the Indonesia economy, especially in agriculture sector, one of them is a banana fruit.Data of this research was obtained from books, journals, official documents and websites that support the hyphotesis. The author used liberalism approach from adam smith and nation-state level analyze. The theories used in this research is international economic cooperation.The result of this research shows that impact from the banana exports Indonesia to Japan with the Indonesia-Japan Economic Partnership Agreement (IJEPA) has a some impact to Indonesia and Japan, that impact is an economic politic. Both Indonesia and Japan have mutually obtained significant profit from this banana exports. Indonesia has gained profit by the increasing banana growers income, increasing gross domestic product, increasing a balance of trade Indonesia-Japan, increasing economic cooperation betweem Indonesia-Japan and keep on expand a market of banana products to japan and other country. Japan it self gained profit for becoming the main destination of banana exports from Indonesia that leads the country to increase it is access to Indonesia.Keyword: IJ-EPA, Banana Exports, International Economic Cooperation, National Inco